Hal-Hal Yang Ada Hubungan Dengan Stroke Iskemik Pada Penderita Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2010 Sampai Dengan Tahun 2020 - Idsam, Suci Anugrah; Sartika , Suriana Dwi; Supardin, Supardin (Bosowa Medical Journal, 2023)
Ischemic stroke or non-hemorrhagic stroke is a disease that occurs due to blocked or stopped blood flow to the brain. If the blood flow is blocked, the brain cells (neurons) cannot work properly and if it lasts for more than a few minutes, the brain cells will be ischemic. The purpose of this study was to find out the things that have a relationship with ischemic stroke in patients in several locations in Indonesia for the period 2010 to 2020. The research method used is an analytical study with a literature review from ten scientific research journals using a case control design. The result from ten scientific research journals test founded that there were significant correlation between hypertension (p-value = <0.000) and family history (p-value = <0.000) with ischemic stroke in patients. Then, there was no significant correlation between obesity, diabetes mellitus, heart disease, and smoking on ischemic stroke in patients with p-value > 0.05 in several locations in Indonesia. From this research concluded that hypertension and family history of stroke are related to ischemic stroke patients in several locations in Indonesia for the periods 2010 to 2020